PENINGKATAN PRESTASI BELAJAR PKN MENGGUNAKAN MODEL KOOPERATIF STUDENT TEAM ACHIEMENT DIVISION (STAD) - Suwendra, I Nyoman (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2018)
The classroom action research carried out has the purpose to improve student learning achievement. Low initial data acquisition for grade IVB students in Semester I Elementary No. 4 Sibanggede 2015/2016 Academic Year makes researchers try to improve the unfavorable processes that have been implemented. Improvement of the learning process is carried out through the application of the Student Team Achiement Division (STAD) Cooperative learning model. This model is expected to solve the problems at hand. After the data was collected through learning achievement test instruments, it was obtained an increase in learning outcomes with initial data that the average class reached 72.57 with a percentage of new learning completeness reaching 33.33%, in cycle I it increased to 76.24 average class and 61.90% for completeness of learning. Whereas in the second cycle the data has increased to 82.24 the average class and 90.48% of the completeness of the study. The data in Cycle II has shown the successful implementation of learning which exceeds the required indicators. Therefore the researchers concluded that the application of the Student Team Achiement Division (STAD) Cooperative learning model in carrying out the learning process was able to improve students' learning achievement.